Principles of construction hybrid power installations - Smyrnov, O.; Klymenko, S.; Смирнов, О. П.; Клименко, С. І.; Клименко, С. И. (Харківський національний автомобільно-дорожній університет, 2015)
A new classification of the hybrid power plant, that defines of their creating at the main decisive principle: economic, energy and ecological. At creating hybrid vehicles in the budget segment, the most promising is the economic principle of the hybrid power plant.
Принципи побудови гібридних силових установок
Принципы построения гибридных силовых установок
Keywords: hybrid vehicle; hybrid electric; hybrid power plant; construction principle; internal combustion engine; electric motor; traction battery; гібридний транспортний засіб; гібридний електромобіль; гібридна силова установка; принцип побудови; двигун внутрішнього згоряння; електричний двигун; тягова акумуляторна батарея; гибридное транспортное средство; гибридный электромобиль; гибридная силовая установка; принцип построения; двигатель внутреннего сгорания; электродвигатель; тяговая аккумуляторная батарея; 629.3, 504